Investigation and diagnostic imaging of suspected pulmonary embolism during pregnancy and the puerperium: A review of the literature. Issue 4 (20th April 2020) - Tester, Jodie; Hammerschlag, Gary; Irving, Louis; Pascoe, Diane; Rees, Megan
Summary: Pulmonary embolism (PE) is a leading cause of maternal mortality with women at increased risk of PE during pregnancy and the early postpartum period. Clinical assessment of suspected PE during pregnancy is challenging as signs and symptoms associated with PE overlap with physiological changes of pregnancy. Clinical tests and rules commonly used to assess pre‐test probability of PE were historically not well validated in the pregnant population. The challenges of clinical assessment in the pregnant and postpartum population result in a lowered threshold for diagnostic imaging. Computed tomographic pulmonary angiography (CTPA) and nuclear medicine lung scintigraphy or ventilation/perfusion (V/Q) scans are the main types of diagnostic imaging for suspected PE. Both methods are associated with small levels of ionising radiation exposure to mother and foetus. Accuracy of the diagnostic imaging tests is paramount. Haemodynamic changes of pregnancy, including increased heart rate, increased blood volume and altered flow velocity in the pulmonary arteries, may influence the quality of imaging. This comprehensive review examines the literature and evidence for the investigation and diagnostic imaging of suspected pulmonary embolism during pregnancy with CTPA and V/Q. Clinical decision‐making tools, biomarkers and diagnostic imaging during pregnancy and postpartum will be considered with a focus on diagnostic accuracy and yield, radiation dose exposure (maternal–foetal) and protocol modifications. Current practice guideline recommendations and recent literature on diagnostic pathways are also presented.